The mediating effect of resilience and self-efficacy between physical activity and wellbeing: a meta-analytic structural equation modeling - Cui, Zhibo; Li, Zhihua; Wang, Tong; Li, Kaixin; Zheng, Haoyu; Yang, Chengbo (Frontiers in Psychology, 2025)
BackgroundWhile the positive relationship between physical activity and wellbeing is well-established, the mediating roles of self-efficacy and resilience remain insufficiently understood. This study employed a meta-analytic structural equation modeling (MASEM) approach to investigate whether these psychological factors mediate the relationship between physical activity and wellbeing, aiming to clarify the underlying mechanisms that contribute to this association.MethodsTo achieve this, we systematically searched five databases, Web of Science, PsycINFO, SportDiscus, PubMed, and CNKI, without restrictions on language or publication date. Relevant correlation coefficients were extracted from eligible studies. A meta-analysis was conducted to evaluate the direct relationship between physical activity and wellbeing, followed by a two-stage MASEM to assess the mediating effects of self-efficacy and resilience.ResultsA total of 20 studies comprising 23,377 participants revealed a significant positive correlation between physical activity and wellbeing (r = 0.347, p < 0.001). Subgroup analyses indicated stronger associations in on-site samples (r = 0.384) and within Eastern cultures (r = 0.452). Path analysis demonstrated that physical activity directly enhanced wellbeing (unstandardized effect = 0.168, p < 0.001), and also had significant indirect effects via self-efficacy (standardized indirect effect = 0.196, p < 0.001) and resilience (standardized indirect effect = 0.068, p < 0.001). No significant differences were found between models of subjective wellbeing and psychological wellbeing (p > 0.05). These findings underscore the critical mediating roles of self-efficacy and resilience in the physical activity-wellbeing pathway and offer valuable insights for designing targeted interventions to enhance mental health outcomes through physical activity.ConclusionPhysical activity is positively associated with wellbeing, with stronger effects observed in on-site sampling and within Eastern cultural contexts. Moreover, self-efficacy and resilience serve as mediating factors in the relationship between physical activity and wellbeing.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251016483.